PENGARUH DPK, CAR, ROA TERHADAP PEMBIAYAAN MUDHARABAH PADA BANK UMUM SYARIAH YANG TERDAFTAR DI OTORITAS JASA KEUANGAN PERIODE 2013-2017 - Ardia Rahma Wardani, 15.05.52.0131; Poerwati, Rr. Tjahjaningi (Students' Journal of Accounting and Banking, 2019)
This research aims to examine the effect of third party fund, capital adequacy ratio, and return on asset to financing mudharabah at Shari’s Commericial Bank in 2013-2017. The population in this research are Shari’s Commericial Bank (Otoritas Jasa Keuangan). Sampling method using purposive sampling in 2013 until 2017 and obtained as many as 31 banks. The technique of data analysis is multiple linear regression analysis. The results of this research indicate that Third Party Fund have a positive influence on Mudharabah Financing. Capital Adequacy Ratio have negative effect on Mudharabah Financing while Return On Asset have no effect on Mudharabah Financing.